Characterizing the ionization potential depression in dense carbon plasmas with high-precision spectrally resolved x-ray scattering. (13th November 2018) - Kraus, D; Bachmann, B; Barbrel, B; Falcone, R W; Fletcher, L B; Frydrych, S; Gamboa, E J; Gauthier, M; Gericke, D O; Glenzer, S H; Göde, S; Granados, E; et al.
Abstract: We discuss the possibility of obtaining highly precise measurements of the ionization potential depression in dense plasmas with spectrally resolved x-ray scattering, while simultaneously determining the electron temperature and the free electron density. A proof-of-principle experiment at the Linac Coherent Light Source, probing isochorically heated carbon samples, demonstrates the capabilities of this method and motivates future experiments at x-ray free electron laser facilities.